Can a senior house officer's time be used more effectively?. Issue 5 (25th August 2004) - Mitchell, J; Hayhurst, C; Robinson, S M
Abstract : Objectives: To determine the amount of time senior house officers (SHO) spent performing tasks that could be delegated to a technician or administrative assistant and therefore to quantify the expected benefit that could be obtained by employing such physicians' assistants (PA). Methods: SHOs working in the emergency department were observed for one week by pre-clinical students who had been trained to code and time each task performed by SHOs. Activity was grouped into four categories (clinical, technical, administrative, and other). Those activities in the technical and administrative categories were those we believed could be performed by a PA. Results: The SHOs worked 430 hours in total, of which only 25 hours were not coded due to lack of an observer. Of the 405 hours observed 86.2% of time was accounted for by the various codes. The process of taking a history and examining patients accounted for an average of 22% of coded time. Writing the patient's notes accounted for an average of 20% of coded time. Discussion with relatives and patients accounted for 4.7% of coded time and performing procedures accounted for 5.2% of coded time. On average across all shifts, 15% of coded time was spent doing either technical or administrative tasks. Conclusion: In this department an average of 15% of coded SHOs working time was spent performing administrative and technical tasks, rising to 17% of coded time during a night shift. This is equivalent to an average time of 78 minutes per 10 hour shift/SHO. Most tasks included in these categories could be performed by PAs thus potentially decreasing patient waiting times, improving risk management, allowing doctors to spend more time with their patients, and possibly improving doctors' training.